Exploring My Images of Mathematics and Its Influence on Learning - Lamichhane, Basanta Raj (Saptagandaki Journal, 2020)
The major aim of this paper is to explore my images of mathematics and its influences on my teaching-learning strategies. I have employed an auto/ethnographic research design to excavate my lived experiences largely informed by interpretive and critical paradigms. To generate field texts dialectical and historical-hermeneutic approaches have been used. The Habermas’ knowledge constitutive interest and Mezorows’ transformative learning theory were used as theoretical referents. The writing as a process of inquiry has been used to create layered texts through thick descriptions of the contexts, critical self-reflexivity, transparent and believable writing aiming to ensure the quality standards of the research. The research illuminates that most of the negative images of mathematics have been emerged by the conventional transmissionist ‘one-size-fits-all’ pedagogical approach. Likewise, it has indicated that to transform mathematics education practices towards more empowering, authentic, and inclusive ones, it must be necessary to shift in paradigms of teaching and practitioners’ convictions, beliefs, values, and perspectives as well.